Motivational interviewing intervention for the management of hypertension: a meta-analysis - Xu, Ju; Gu, Xiaoyan; Gu, Jiaying; Zhao, Lijuan; Li, Mianxian; Hong, Cheng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundImproving medication compliance and self-efficacy in hypertensive patients is of significant importance for their prognosis. This meta-analysis aimed to assess the role of motivational interviewing in reducing systolic and diastolic blood pressure, self-efficacy, quality of life and medication adherence in hypertensive patients.MethodsTwo authors searched PubMed, Cochrane Library, Clinicaltrials, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database, Weipu and Wanfang Database up to May 28, 2024 for randomized controlled trials (RCTs) evaluating the role of motivational interviewing on hypertensive patients. The search was restricted to articles published in English and Chinese languages. RevMan 5.4 software was used for meta-analysis.ResultsA total of 16 RCTs were included. The meta-analysis findings demonstrate that motivational interviewing could reduce both systolic pressure [MD = −3.26, 95% CI (−5.16, −1.36), P < 0.001] and diastolic blood pressure [MD = −1.78, 95% CI (−3.48, −0.08), P < 0.001] levels in hypertensive patients, while simultaneously enhancing their self-efficacy [MD = 2.92, 95% CI (1.84, 4.00), P = 0.001], quality of life [MD = 6.99, 95% CI (3.25, 10.74), P = 0.003], and medication compliance [OR = 4.30, 95% CI (1.53, 12.10), P = 0.003]. No significant publication bias across the synthesized outcomes were found by Egger regression analyses (all P > 0.05).ConclusionsMotivational interviewing has been shown to effectively reduce blood pressure in the short term among individuals with hypertension, while simultaneously enhancing their self-efficacy, quality of life, and adherence to medication regimens.